2021
DOI: 10.3390/children8090819
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series on Genotype and Outcome of Liver Transplantation in Children with Niemann-Pick Disease Type C

Abstract: Background: To report on clinical presentation and outcomes of children who underwent liver transplantation (LTx) and were subsequently diagnosed to have Niemann-Pick type C (NPC). Methods: Retrospective, descriptive, multi-centre review of children diagnosed with NPC who underwent LTx (2003–2018). Diagnosis was made by filipin skin test or genetic testing. Results: Nine children were identified (six centres). Neonatal acute liver failure was the most common indication for LTx (seven children). Median age at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, it needs to be highlighted that NPC diagnosis was made after LTX in eight out of nine patients. Seven children were still alive (a median follow-up time of 9 (range: 6–13) years), while neurological symptoms developed in four out of seven patients at a median of 9 (range: 5–13) years following LTx [ 67 ]. Yamada et al reported three patients with neonatal-onset NPC in whom LTx was performed as a life-saving procedure.…”
Section: Treatment Of Lysosomal Diseases Regarding Liver Involvementmentioning
confidence: 99%
“…However, it needs to be highlighted that NPC diagnosis was made after LTX in eight out of nine patients. Seven children were still alive (a median follow-up time of 9 (range: 6–13) years), while neurological symptoms developed in four out of seven patients at a median of 9 (range: 5–13) years following LTx [ 67 ]. Yamada et al reported three patients with neonatal-onset NPC in whom LTx was performed as a life-saving procedure.…”
Section: Treatment Of Lysosomal Diseases Regarding Liver Involvementmentioning
confidence: 99%
“…It has also allowed for a molecular diagnosis to be obtained in patients with liver disease of an otherwise uncertain cause; the ability to obtain a diagnosis in these cases can ensure that appropriate therapies are instituted while therapies which do not offer benefit are avoided. For instance, liver transplantation is not generally associated with favourable outcomes in conditions such as mitochondrial deoxyribonucleic acid (DNA) depletion syndrome [37,38] or NPC [39]. A brief description of past, current and emerging sequencing methods is provided in Figure 1.…”
Section: The Role Of Next-generation Sequencing In the Work-up Of Cholestasismentioning
confidence: 99%